Exploring the Impact of Digital Transformation on Business Operations and Customer Experience - Kothapalli, Kanaka Rakesh Varma (Global Disclosure of Economics and Business, 2022)
This study examines how digital transformation affects corporate operations and customer experience to determine its main pros and cons. Digital developments’ effects on operational efficiency and customer happiness are assessed using secondary data from current research and case studies. Digital transformation enhances operational processes via automation, data analytics, and customer experience through customization, AI-powered support, and seamless integration across numerous channels. Significant challenges include high installation costs, business performance variation, and data privacy risks. The report proposes many policy consequences, such as providing financial assistance to small and medium-sized firms (SMEs), enforcing standard norms for data security, and encouraging research unique to different industries. These steps reduce difficulties and make it easier for enterprises to embrace digital technology. The goal is to enable organizations to fully use digital transformation to achieve operational excellence and improve customer engagement.